Enhanced recovery after surgery in colorectal cancer. Instituto Nacional de Enfermedades Neoplásicas - Guevara Jabiles, Andrés (2021)
Aim: Describe and analyze the safety of the “Enhanced Recovery After Surgery” (ERAS) protocol in elective procedures for colorectal cancer. Materials and Methods: Observational study of 272 patients with colorectal cancer who underwent elective surgery from January 2019 to September 2020 at the “Instituto Nacional de Enfermedades Neoplásicas”, Peru, were retrospectively collected. U Mann-Whitney test, Pearson chi-square test and odds ratios (OR) were used for statistical analysis. Results: 90 patients were included in the ERAS program with a median postoperative hospital stay of 3 days (range 3-19). Laparoscopic surgery was performed in 53% of the patients with significantly shorter postoperative hospital stay in comparison with the patients who had open surgery (p=0,035). Oral food intake less than 24 hours postoperatively was 91%, and early mobilization in 89% of the cases. The postoperative complication rate was 29%, higher in rectal/anus resection than in colonic resections (40% vs 20%, p=0,043) (OR=2,67, CI 95%: 1,02 – 7,01). Eight patients had a major postoperative complication, four with anastomotic leakage and four required hospital readmission. Conclusions: The perioperative management of ERAS program for colorectal cancer in elective surgery is safe and feasible with acceptable morbimortality risk.